التجريد من الجنسية في التشريعات الحديثة دراسة مقارنة في تشريعات (سوريا، المغرب) - الخابور ساجر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يُثير نظام التجريد من الجنسية خلافاً فقهياً كبيراً بين من يؤيد حق الدولة بتجريد الأفراد الذين يشكلون خطراً على أمن الدولة وسلامة المجتمع وانسجامه من جنسيتها ، وبين أولئك الذين يرون في التجريد سلاحاً خطيراً بيد الدولة مسلطاً على رقاب مواطنيها على ما من شأنه المساس بحق أساسي من حقوق الإنسان وهو حق الإنسان في أن يكون له جنسية. وسنتناول في هذا البحث تطور نظام التجريد من الجنسية في التشريعات الحديثة وأثر هذا التطور على التشريعات العربية، حيث سنقوم أولاً بتحديد مفهوم التجريد من الجنسية وتمييزه عن المفاهيم المشابهة له، ثم نقوم ببيان حجج أنصار حق الدولة في تجريد مواطنيها من الجنسية وحجج معارضيه وسنستعرض التطورات التي مرت على نظام في التشريعات الغربية ونبين أهم الحالات التي تسمح بموجبها هذه التشريعات للسلطة بتجريد الأفراد من جنسيتهم. وأخيراً سنقوم باستعراض أهم الاتجاهات السائدة في التشريعات العربية ومدى تأثرها بالاتجاه السائد في التشريعات الغربية. The denaturalization system raises a huge jurisprudential controversy between advocating state’s right to deprive the individuals who endanger its security and community safety and consistency of its citizenship and those seeing the denaturalization as a serious weapon in state’s hand threatens its nationals and affects a basic human right of having a citizenship. In this research , we are going to discuss the development of the denaturalization system in the modern legislations and impact of that development on the Arab legislations; as we will first define the denaturalization concept and distinguish it from the similar concepts; we will then demonstrate the arguments of those supporting state’s right to deprive its nationals of citizenship and the arguments of those disapproving of the same. We will mention the developments that have occurred to the denaturalization system in the western legislations and show the most important cases such legislations under which permit the authority to denaturalize its nationals; and finally we will examine the most significant trends in the Arab legislations and how are affected by the dominant stream of the western legislations.